Diversidade de Erysiphe spp., agentes etiológicos do oídio do cajueiro - Fonseca, Wéverson Lima (2019)
Powdery mildew is currently the most important cashew disease in all producing regions of Brazil. Although it was first reported more than a century ago, up to the beginning of the twenty-first century there were no epidemics in Brazil that caused a major economic impact. Differences in morphological and pathogenic of the causal agent showed raise the possibility of different species of the genus Erysiphe would be associated to the cashew powdery mildew. Resulting, therefore, in strong evidence of involvement of different hosts in the cashew disease epidemiology. This study was developed to elucidate these questions, comparing by molecular phylogeny the morphological types associated with the cashew tree powdery mildew in Brazil. The phylogenetic relationships were reconstructed in fungi causing powdery mildews in plants that occur in the cashew tree ecosystem, aiming to know their relations with the hosts, provoking possible involvements of alternative hosts with the epidemics verified in the cashew tree. The work consisted initially of collecting samples of plants with symptoms of powdery mildew, pathogenicity tests in the original hosts, followed by morphological, phylogenetic and cross-inoculation analyzes. Based on these analyzes, two species have been shown to be associated with cashew powdery mildew: Erysiphe quercicola, which infects young immature tissues, such as bright leaves, flowers and young fruits; and Erysiphe necator, which infects mature and shaded foliar tissues. This is the first report on the occurrence of both E. quercicola and E. necator causing powdery mildew in cashew trees, and the first detection of E. necator in this host. These studies allowed the first identification of alternative hosts of E. quercicola as Bixa orellana, Clitoria fairchildiana and Mangifera indica. Cross-inoculation tests served to raise the possibility of involvement of these plant species as the primary source of cashew powdery mildew inoculum.